Late Quaternary palaeoenvironmental change in the year-round rainfall zone of South Africa derived from peat sediments from Vankervelsvlei. (15th August 2019) - Strobel, P.; Kasper, T.; Frenzel, P.; Schittek, K.; Quick, L.J.; Meadows, M.E.; Mäusbacher, R.; Haberzettl, T.
Abstract: Due to the scarcity of natural archives for palaeoenvironmental studies, the climatic evolution of South Africa during the late Quaternary remains the subject of considerable debate. Peat deposits provide excellent archives to investigate past environmental and climate variability. Vankervelsvlei, a fen near the southern Cape coast, located 152 m above mean sea level within the year-round rainfall zone of South Africa, is ideally suited to investigate past environmental changes in this region. A 14.6 m long sediment sequence was retrieved from the fen, from which 8.85 m of sediment have been analysed using a multi-proxy approach. This includes elemental, macrofossil and micropalaeontological analyses. As a novelty in palaeoenvironmental reconstruction in this region, leaf wax n -alkanes and their compound-specific stable carbon and hydrogen isotopes were also investigated. The chronology of the sequence is based on 13 radiocarbon ages and reveals a basal age of 37, 430 +1, 570 /-1, 710  cal BP. The top of the investigated sequence has an age of 1, 180 +340 /-170  cal BP. Leaf wax n -alkane abundances and their compound-specific stable carbon and hydrogen isotopes, as well as various (in)organic (bio)geochemical parameters, indicate that the older section of the sequence (37, 430 +1, 570 /-1, 710 - 28, 050 +510 /-600  cal BP), which is composed of strongly degraded peat, represents a rather dry phase during MIS 3. This is followed by a hiatus of around 20, 000 years (28, 050 +510 /-600 to 8, 360 +730 /-810  cal BP) reflecting the driest conditions during MIS 2. By comparing to supra-regional archives, this is hypothesised to have resulted from a larger extension of the Antarctic sea ice, which caused an equatorward shift of the Westerlies, blocking the tropical easterlies and resulting in drier conditions along the south coast and the adjacent coastal platform. During the Early Holocene, the input of reworked soil into the depression and subsequently renewed peat formation from 6, 820 +305 /-365  cal BP to 1, 180 +340 /-170  cal BP in Vankervelsvlei point to moister climatic conditions. Contraction of Antarctic sea ice and a poleward shift of the Westerlies during the Holocene is consistent with this interpretation. Climatic driving forces are suggested to differ between centennial/millennial and orbital time scales. Evapotranspirative enrichment through stronger winds is assumed to be the main driver on centennial to millennial time scale within this hydrological system. However, a combination of evapotranspiration and precipitation amount seems to be the most prominent driver on the orbital time scales. Highlights: Multi-proxy approach including compound-specific isotopes from leaf wax n -alkanes. Westerly movement affects the southern African climate. MIS 3 dry, MIS 2 even drier, MIS 1 wetter, but variable climatic conditions. Leaf wax δ 2 H values are affected by wind-driven evapotranspiration.